The Effect of Deep Breathing Relaxation Techniques on Blood Pressure Changes in Elderly Patients with Hypertension - Sumiati, Eti; Nurlianti; Dewi Nur Anggraeni (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
Hypertension is a condition characterized by an abnormal increase in blood pressure, which can lead to higher morbidity and mortality rates. The number of individuals affected by hypertension continues to rise annually, with projections estimating that by 2025, approximately 1.5 billion people will be affected, and 9.4 million deaths will occur each year due to hypertension and its complications. Among the elderly population, hypertension prevalence is notably increasing. This study aims to assess the impact of deep breathing relaxation techniques on blood pressure changes in elderly hypertension patients at the Geriatrics Clinic of Mataram Regional Hospital. A one-group pretest-posttest design was utilized, in which blood pressure measurements were taken before and after the intervention. The study involved 42 elderly hypertension patients, with data analysis conducted using the T-test. The findings revealed a significant effect of deep breathing relaxation on blood pressure reduction, as indicated by a p-value of 0.000. In conclusion, deep breathing relaxation techniques play a significant role in lowering blood pressure among elderly hypertension patients